Antithyroid drug therapy of Graves'' hyperthyroidism: realistic goals and focus on evidence. Issue 1 (January 2006) - Laurberg, Peter; Andersen, Stig; Karmisholt, Jesper
Only a minority of patients with hyperthyroidism caused by Graves' disease will experience cure of disease with a permanent euthyroid state without medication. Antithyroid drugs are useful in attaining euthyroidism, and most patients will gradually enter remission of the autoimmune abnormality after becoming euthyroid. A stable euthyroid state may be sustained by prolonged low-dose medication. The risk of relapse of hyperthyroidism after withdrawal of medication seems to be independent of duration of therapy, once remission has been induced. A number of risk factors influence the outcome of therapy and they should be evaluated when planning duration of therapy with antithyroid drugs.